PP4 and Vila Expo'98: 20 years of an urban design idea - Pinto, Pedro (2020)
In 2018, 20 years passed since the inauguration of Expo'98. The conversion of Lisbon's eastern riverside front, which transformed 340 hectares of industrial and port land into an urban fabric. The operation would be structured with a general plan, five detailed plans and five public space projects. This paper deals with the Detailed Plan 4 (1994) and the Public Space Project (1996) corresponding to Zone 4 of Expo'98. Plan and project would became a residential area for the employees of the world exhibition, and after the event would be placed on the market. In the post-Expo years, the area would have a remarkable commercial success. As an urban morphology, the plan aimed at an urban design that would provide variety and complexity, understanding the public space as a formal thing. The proposed urban idea was intended to be conciliatory: between the historical Lisbon city models and the modern Lisbon of the 1950s; between the surrounding urban structures and the projected new city; between a continuous system of public spaces and a conformation of buildings in semi-open blocks or, even, between a profit-oriented urban operation and the incorporation of landscape and environmental values, at an unusual scale.